Development as a fraud and the decolonial way out - Santos, Nathan (2021)
This article recovers the debate on the concept of development, opposed by Latin American decolonial theories. America was the privileged locus for the continuity of colonial subservient relations in capitalism. When the imperial and metropolitan rule in the former colonies were removed, the processes of independence triggered the development of capitalism beyond Europe. With the relations of production of wage and private property, the patterns of consumption and the consolidation of modern nation-states in the New World, came the capitalist worldview. A unilinear history, a single way of life and only a pattern of knowledge production and social organization. We argue, therefore, that instead of a goal, development is a farce that constrained economic and social thinking in Latin America to the unfinished, imperfect and colonial reproduction of Eurocentric bourgeois civilization. Overcoming this farce lies in the decolonization of knowledge and in revolutionary praxis.